Integration of islamic values in organizational image and reputation management: a conceptual study from a modern public relations perspective - M. Yakub; Ahmad Sampurna (Indonesian Institute For Counseling, Education and Therapy, 2026)
This paper examines the concepts of image and reputation within the framework of Public Relations (PR) and their relevance to Islamic values. Image is understood as the public’s perception shaped by experience and information, while reputation represents the long-term accumulation of assessments based on an organization’s consistent performance and behavior. In modern PR practice, both concepts serve as essential foundations for building public trust and social legitimacy. Using a qualitative approach through library research, this study analyzes theories of image, reputation, and PR management, and integrates them with Islamic ethical principles such as ṣidq (honesty), amanah (responsibility), ‘adalah (justice), ihsan (benevolence), as well as the values of dakwah and amar ma’ruf nahi munkar. The findings indicate that Islamic values are not only compatible with but also enrich contemporary PR practices by providing strong ethical and spiritual foundations. The integration of Islamic principles encourages communication that is honest, transparent, and dignified, preventing PR activities from relying on manipulative strategies. This approach also serves as a critique of Western paradigms that often emphasize utilitarian and instrumental objectives. Consequently, the incorporation of Islamic values in Public Relations contributes to strengthening an organization’s image and reputation sustainably while fostering a morally grounded and socially beneficial civilization.